2021
DOI: 10.3389/fphar.2021.778165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D3 and Meso-Zeaxanthin on Human Retinal Pigmented Epithelial Cells in Three Integrated in vitro Paradigms of Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is a degenerative retinal disease and one of major causes of irreversible vision loss. AMD has been linked to several pathological factors, such as oxidative stress and inflammation. Moreover, Aβ (1–42) oligomers have been found in drusen, the extracellular deposits that accumulate beneath the retinal pigmented epithelium in AMD patients. Hereby, we investigated the hypothesis that treatment with 1,25(OH) 2D3 (vitamin D3) and meso-zeaxathin, physiologically present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Consistent with previous studies, which showed an antiinflammatory diet alleviated retinopathy in aged or diabetic participants, we found a diet with anti-inflammatory potential was associated with a decreased prevalence of retinopathy in DM or aged participants. Adherence to a Mediterranean diet or antioxidant supplement with Omega-3 unsaturated fatty acids and vitamins could improve age-related macular degeneration and DR (12)(13)(14)(15)(16)(17). DII is an integrated index to evaluate dietary inflammatory potential, which might synthetically reflect consumption lifestyle and give instructions to patients at high risk of retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, which showed an antiinflammatory diet alleviated retinopathy in aged or diabetic participants, we found a diet with anti-inflammatory potential was associated with a decreased prevalence of retinopathy in DM or aged participants. Adherence to a Mediterranean diet or antioxidant supplement with Omega-3 unsaturated fatty acids and vitamins could improve age-related macular degeneration and DR (12)(13)(14)(15)(16)(17). DII is an integrated index to evaluate dietary inflammatory potential, which might synthetically reflect consumption lifestyle and give instructions to patients at high risk of retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ROS production activates different signaling pathways. Typically, H 2 O 2 activates the NF-κB signaling pathway, as demonstrated in different experimental models, including ARPE-19 cells [ 29 , 30 ]. In addition, upstream kinases that are oxidized by ROS can also activate the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that vitamin D3 and meso-zeaxanthin were effective in lowering inflammatory cytokines, Il-1β and TNF-α. 57 The effects of MSN-CPBA-VD-Dex (containing 50 nM VD) in preventing IL-6 secretion from retinal epithelial cells were significantly higher than those of VD (50 nM) alone, suggesting once again the elevated bioavailability of VD that was accomplished by using MSN-CPBA-VD-Dex.…”
Section: Effect Of Msn-cpba-vd-dex In Inhibitingmentioning
confidence: 94%